1998
DOI: 10.1046/j.1365-2540.1998.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between dispersal and mitochondrial gene flow: isolation by distance in a tropical teleost, Lates calcarifer (Australian barramundi)

Abstract: Patterns of population subdivision and the relationship between gene flow and geographical distance in the tropical estuarine fish Lates calcarifer (Centropomidae) were investigated using mtDNA control region sequences. Sixty-three putative haplotypes were resolved from a total of 270 individuals from nine localities within three geographical regions spanning the north Australian coastline. Despite a continuous estuarine distribution throughout the sampled range, no haplotypes were shared among regions. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 29 publications
(6 reference statements)
5
33
1
Order By: Relevance
“…Australian barramundi populations (0·004-0·064) given by Shaklee & Salini (1985), Shaklee et al (1993) and Keenan (1994), but are similar to mtDNA sequence-based φ ST estimates for the same populations given by Chenoweth et al (1998a;0·328). These results may indicate that population subdivision is greater for mtDNA than for nuclear genes, which is a common empirical finding (Hallerman & Beckmann, 1988;Billington & Hebert, 1991;Nielsen et al, 1996;Chenoweth & Hughes, 1997).…”
Section: Population Subdivision and Gene Flowsupporting
confidence: 57%
See 1 more Smart Citation
“…Australian barramundi populations (0·004-0·064) given by Shaklee & Salini (1985), Shaklee et al (1993) and Keenan (1994), but are similar to mtDNA sequence-based φ ST estimates for the same populations given by Chenoweth et al (1998a;0·328). These results may indicate that population subdivision is greater for mtDNA than for nuclear genes, which is a common empirical finding (Hallerman & Beckmann, 1988;Billington & Hebert, 1991;Nielsen et al, 1996;Chenoweth & Hughes, 1997).…”
Section: Population Subdivision and Gene Flowsupporting
confidence: 57%
“…Estimates of mtDNA variation (h and π) for barramundi were generally higher than those reported for a range of coastal and marine species including the catadromous eel Anguilla rostrata (Le Sueur) (see Table 2 in Avise, 1992), but are similar to values estimated by Chenoweth et al (1998a) for the mtDNA control region in Australian barramundi populations. The absence of mtDNA variation in the population from Cairns may be due to the small sample size, although Chenoweth et al (1988b) also reported low mtDNA diversity in eastern Australian populations of barramundi, possibly resulting from a population bottleneck during recent evolution.…”
Section: Characteristics Of Barramundi Mtdnasupporting
confidence: 51%
“…Pleistocene, the wide continental shelf to Australia's north including the Torres Strait was exposed, making Papua New Guinea and Australia a single land mass (van Oosterzee 1997). This vicariant event is reflected in the population genetics of at least three tropical Australian fishes -the saddle-tail sea perch (Lutjanus malabaricus) (Elliott 1996); barramundi (Chenoweth et al 1998b) and Spanish mackerel (J. R. Ovenden, R. Street, R. C. Buckworth, C. Foschia and S. J. Newman, unpublished data) -and of green turtles (Norman et al 1994). The frequencies of the three most common RFLP (restriction fragment length polymorphism) haplotypes in sea perch mtDNA were 61, 15 and 12% in a sample from the Queensland east coast (near Townsville), Fig.…”
Section: Population Genetic Structurementioning
confidence: 99%
“…Tropical Pacific sea urchins also show a pattern of isolation by distance, in which F ST measured with mitochondrial sequence data increases markedly with geographic distance between pairs of populations (Palumbi et al, 1997). Isolation by distance was also detected in Atlantic cod (Gadus morhua) and coral reef species Australian barramundi (Lates calcarifer) (Pogson et al, 2001;Chenoweth et al 1998).…”
Section: Discussionmentioning
confidence: 89%